Análisis comparativo entre los criterios internacionales y los requerimientos para la descarga de sedimentos de embalses en Colombia (2019)
The loss of volume in reservoirs due to sedimentation has become a concern for many countries, including Colombia. Therefore, it is necessary to implement sediment management strategies in order to recover the lost volume and restore sediment flow downstream the dam. Flushing in reservoirs is one strategy with great potential for implementation, compared with other methods, due to its easy execution and optimal value given its economic cost. Based on main hydrosedimentological considerations for flushing, a comparative analysis between three of the most representative cases worldwide (Génissiat - France, Dashidaira - Japan and Alamo - United States of America) and colombian cases of Calderas (Antioquia) and Bajo Anchicayá (Valle del Cauca) is presented. It is worth noting that the colombian cases were developed in the framework of the authorization process of a protocol for flushing, supervised by the Environmental Authority in Colombia. In this study it has been identified criteria and requirements related to flushing, such as, maximum sediment concentrations, peak flows generated during the discharge, monitoring schemes performing impact evaluation downstream of the dam. Also, it has been stressed the importance of generating protocols in order to mitigate the impact of excess of sediment in the reach produced by flushing and performing as many pilot tests as necessary to have enough information to define the conditions of execution. The criteria applied and the values for each case are different depending on the purpose, the type of flushing performed and the conditions of each site. However, the execution of flushing during a period of high flows affluent to the reservoir is a commonality. In flushing, the experimental study is the best way to achieve the most appropriate conditions for execution, to define the possible effects on the ecosystems downstream the dam and to find ways to mitigate them. Although, using flushing to recover the total loss of the reservoir volume due to sediments